Evaluation of Bone Resorption in Type I diabetes Mellitus Patients by Measuring Urinary Total Deoxypyridinoline ( U. DPD) as a Biomarker of Bone Resorption - Zainab Ali Kadhem (مجلة علوم ذي قار, 2019)
Background: Diabetes mellitus is a common disease in most parts of the world, the metabolic abnormalities of diabetes potentially affect bone metabolism, structure, mineral density, and bone resorption, as part of physiological bone turnover. Aim: This study aimed to estimate urinary total deoxypyridinoline as a biomarker of mature bone collagen degradation and bone resorption in type I diabetes mellitus patients and evaluate its relationship with fasting blood sugar, serum bone minerals profile and the duration of disease and also to investigate  the degree of severity of bone resorption and the probability of  fracture risk. Patients and methods:165patients with type I diabetes mellitus from Diabetes mellitus and Endocrine Disease Centre at AL -Nasiriyah city in Thi-Qar province, Iraq were studied.100 (60.6%) were female and 65(39.4%) were male, age was between(25-65) year, mean44.27±11.1,their duration with type 1 DM disease ranged from 5 months to 10 years, they were classified into three groups: the first group included 45 (27.3 %)  patient their duration with type 1 DM  were  less than one year, the second group included 65 (39.4%) their duration with type I DM were 1 to 5 year and the third group included 55 (33.3%) patient their duration with disease were from 6 to 10 year. Fasting blood venous and first-morning urine samples were collected for biochemical investigation according to standard methods and Urine DPD was measured by the quantitative competitive enzyme immunoassay. Also, this study included 165 normal people selected as a control group.  The study duration was from May to December 2017. Results: A significant increased (P<0.05) in fasting blood sugar (266.96±33.8 mg/dl), inorganic phosphorous (9.5±0.72mg/dl), and U.DPD (132.34±18.67ng/ml) were seen in type 1 diabetic patients as compared to control group (80 ±5.31mg/dl, 3.38 ± 0.22 mg/dl, and 3.48 ±1.01 ng/ml) respectively. Total calcium (6.10 ± 0.49 mg/dl) and magnesium(1.48 ±0.41 mg/dl) levels in type I diabetic patients  groups were found to be significantly  lower (P < 0.05) than  control group (8.89 ± 0.39 mg/dl and 1.87 ± 0.21 mg/dl) respectively. U.DPD positively related to fasting blood sugar and phosphate, but adverse relation founded with both total calcium and magnesium. There are significantly increased (P < 0.05) in fasting blood sugar, U.DPD, and inorganic phosphorus, also significantly decreased (P < 0.05) in  total calcium and magnesium with the increased prolonged  of disease. Conclusion: Diabetic patients with type I have an elevation in urinary total deoxypyridinoline as a marker of bone resorption and  degradation product of bone matrix which is related to hyperglycemia and abnormal bone mineral profile like hypocalcemia, hyperphosphatemia, and hypomagnesemia, also this  study see that poor glycemic control and type IDM duration seem to play a key role given the lower bone density and  that is mean those patients group underlying bone alterations and  increased  the probability of low bone density and quality then increased  bone fracture risk.